Efforts to Improve Student Learning Outcomes in Getting to Know Angels and Their Duties Through the Make a Match Method in Class X MIA 3 SMA Negeri 1 Kepenuhan - Makmur Makmur (STKIP Rokania Pasir Pangaraian, 2023)
his research uses a qualitative approach with the type of Classroom Action Research (PTK). The research subjects were students of class X MIA 3 SMA Negeri 1 Kecepatan. The data collection technique used in this research is the participant observation method. The data in this research are quantitative data and qualitative data. The research was carried out in four stages. The first stage was pre-cycle using the lecture method with an average score of 558.28 from the Minimum Completeness Criteria (KKM) 75 with student completeness of 11.43%. The second stage of cycle 1 resulted in an average class score of 66.14 which was achieved by 16 students who completed it out of 35 students. With completeness reaching 45.71%. The third stage of cycle II with an average class score of 74.71 was achieved by 23 students who completed it out of 35 students with completeness reaching 65.71% and the fourth stage of cycle III with an average class score of 89.85 achieved 100% completeness. 35 students out of 35 students. Based on this data, by applying the Make a Match method, cycles I, II and III, it can be seen that there is an increase in learning outcomes after implementing the Make a Match method.